CAUSES OF ANGER IN M. IRFAN HIDAYATULLAH’S NOVEL CERMIN RETAK: TABIR ROBBI DAN ROBBANI - Iswandi Iswandi; M. Manugeren; Purwarno Purwarno (JOURNAL OF LANGUAGE, 2020)
This study is concerned with the causes of anger. Anger a basic human emotion, as elemental as, gladness, sadness, anxiety or disgust. These emotions are tied to basic survival and are honed over the course of human history. Anger is related to the “fight, flight, or freeze” response of the sympathetic nervous system:  it prepares humans to fight. But fighting does not necessarily mean throwing punches; it might motivate communities to combat injustice by changing laws or enforcing new behavioral norms. This is the positive trait of anger though in many cases only the negative ones are seen. Everyone experiences anger at some point. It becomes problematic, however, when the frequency or severity of anger interferes with relationships, work performance, legal standing, or mental health. All these points are faced by the main characters of the novel. The whole research is done by means of descriptive qualitative research, exposing the social features, in this case anger. The research results show that there are causes of anger found through the study: past experience and lack of problem-solving ability. Owing to traumatic past experiences, one of the main characters does a kidnapping and on the second point, the inability of solving problems, makes another main character filled with anger.